Epidemiology of Pancreatic Cancer and the Role of Family History - Olson, Sara H. (2012)
Pancreatic cancer is a lethal disease for which only a small number of risk factors have been identified. In addition to older age, male gender, and black race, risk factors include smoking, obesity, long-standing diabetes and pancreatitis, and heavy alcohol use; allergies such as hay fever are related to lowered risk. Several genetic syndromes increase risk of pancreatic cancer. Work on more common genetic variants promises to reveal more potentially important genetic associations.